2023
DOI: 10.1088/2053-1591/acedef
|View full text |Cite
|
Sign up to set email alerts
|

Examination of water absorption of low volume fly ash concrete (LVFAC) under water immersion conditions

Grzegorz Ludwik Golewski

Abstract: The studies were carried out to find a relation between important physical property and the main mechanical parameter of concretes containing fly ash (FA) in order to develop indications for the production of durable composites with the addition of this waste. The tests included low volume fly ash concrete (LVFAC). The cements used in the studies were following: ordinary Portland cement (OPC), (FA-00) and two blended Portland cements containing FA in the amount of: 20%, (FA-20) and 30% (FA-30). Measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(1 citation statement)
references
References 137 publications
0
1
0
Order By: Relevance
“…at 24 h). From the previous studies, it has been established that the use of finer materials such as fly-ash, GGBS, micro-silica, etc aid in effective particle packing in concrete, which in turn reduce the pore volume and inhibit water absorption [49][50][51][52]. Golewski [51,52] reported that the use of finer materials like fly ash helps in reducing the water absorption due to the effective pore packing in concrete and thereby enhancing their durability characteristics.…”
Section: Water Absorptionmentioning
confidence: 99%
“…at 24 h). From the previous studies, it has been established that the use of finer materials such as fly-ash, GGBS, micro-silica, etc aid in effective particle packing in concrete, which in turn reduce the pore volume and inhibit water absorption [49][50][51][52]. Golewski [51,52] reported that the use of finer materials like fly ash helps in reducing the water absorption due to the effective pore packing in concrete and thereby enhancing their durability characteristics.…”
Section: Water Absorptionmentioning
confidence: 99%